NIMG-43. ADVANCED MULTI-PARAMETRIC HYPERPOLARIZED 13C/1H IMAGING OF GBM. (12th November 2021) - Autry, Adam; Vaziri, Sana; LaFontaine, Marisa; Gordon, Jeremy; Chen, Hsin-Yu; Villanueva-Meyer, Javier; Chang, Susan; Clarke, Jennifer; Xu, Duan; Lupo, Janine; Larson, Peder; Vigneron, Daniel; et al.
Abstract: INTRODUCTION: The goal of this study was to characterize progressive and pseudoprogressive GBM using multi-parametric hyperpolarized (HP)- 13 C / 1 H MRI. METHODS: Dynamic HP- 13 C MRI was acquired from 13 patients with progressive GBM [patients (scans): 2(3) IDH-mutant; 11(13) IDH-wildtype] and 2 IDH-wildtype patients (3 scans) demonstrating pseudo-progression following intravenous injection of HP [1- 13 C]pyruvate. Frequency-selective echo-planar imaging (3s temporal resolution, 3.38 cm 3 spatial resolution) captured [1- 13 C]pyruvate metabolism to [1- 13 C]lactate and 13 C-bicarbonate in the brain. Dynamic 13 C data were kinetically modeled to obtain the pyruvate-to-lactate conversion rate constant k PL and temporally summed to calculate 13 C-metabolite percentiles and ratios (linearly interpolated 2x in-plane). 1 H imaging included T2, post-Gd T1, perfusion (nCBV, %recovery), diffusion (ADC), and lactate-edited spectroscopy (CNI, choline-to-NAA index; 1 H-lactate). The normal-appearing white matter (NAWM), non-enhancing lesion (NEL), and contrast-enhancing lesion (CEL) were segmented from 1 H images. 13 C-resolution masks were iteratively applied on a voxel-wise basis to evaluate 1 H imaging parameters within each ROI and multi-parametric data were collectively evaluated using a mixed effects model in R. RESULTS: Progressive IDH-mutant GBM compared to wildtype counterparts displayed increased perfusion %recovery ( p < 0.001) and k PL ( p < 0.01), together with reduced 1 H-lactate ( p < 0.001) and pyruvate percentile ( p < 0.01), in the T2 lesion. Among IDH-wildtype progressive GBM, the CEL was distinguished from NEL/NAWM by increased nCBV ( p < 0.05/0.001), 1 H-lactate ( p < 0.05/0.001); and decreased bicarbonate / lactate ( p < 0.05/0.001). The CEL and NEL were collectively distinguished from NAWM by elevated CNI (p < 0.001/0.001), ADC ( p < 0.05/0.001), pyruvate percentile ( p < 0.001/0.001), lactate percentile ( p < 0.001/0.001), and relative lactate / pyruvate ( p < 0.001/0.05). Psuedo-progressive IDH-wildtype GBM displayed lower k PL (T2 Lesion; p < 0.01) and nCBV (CEL; p < 0.01) compared to progressive GBM. CONCLUSION: HP- 13 C parameters can potentially augment proton imaging and demonstrated Warburg-associated metabolic alterations.